Explosion-Induced Stress Wave Propagation in Interacting Fault System: Numerical Modeling and Implications for Chaoyang Coal Mine - Xiaojun Feng; Qiming Zhang; Muhammad Ali (Shock and Vibration)
Exploring the propagation of stress waves in rocks with preexisting discontinuities is of great importance to reveal rock and geological engineering problems, particularly dynamic disasters like earthquakes and rockbursts in underground coal mining. In this paper, six 3D models established with COMSOL Multiphysics are employed to explore the influence of two preexisting faults with different orientations on the propagation process of explosion-induced stress waves and the reflection effect. Considering the propagation process of stress waves, the interactive effect between two different size faults is discussed. The results show that the dip angles of the preexisting fault and the differences of the elastic modulus, density, and Poisson’s ratio between faults and rocks have great influence on the distribution of stresses and strain-energy density. Immediately after the stress wave induced by blasting arrived at preexisting fault A, a relatively high concentration of the strain-energy density was observed at the last wave before passing through fault A. The presence of faults leads to the reflection of most of the blast energy. When the stress wave propagates across fault A, the strain energy stored in the stress wave becomes attenuated; thus, most strain energy was absorbed by the fault’s domain. Finally, the modeling results were implicated in Chaoyang Coal Mine to account for the distribution of the observed seismic events. This study has guiding significance for the attenuation law of stress waves passing through joint/fissure zones in geological engineering, earthquake engineering, and underground mining engineering.